Effects of polymer concentration and chain length on aggregation in physically associating polymer solutions - Han, X.-G.; Zhang, X.-F.; Ma, Y.-H.; Zhang, C.-X.; Guan, Y.-B. (Condensed Matter Physics, 2011)
The effects of polymer concentration and chain length on aggregation in associative polymer solutions, are studied using self-consistent e^ ld lattice model. Only two inhomogenous morphologies, i.e. microu^ ctuation homogenous (MFH) and micelle morphologies, are observed in the systems with different chain lengths. The temperatures at which the above two inhomogenous morphologies r^ st appear, which are denoted by TMFH and Tm, respectively, are dependent on polymer concentration and chain length. The variation of the logarithm of critical MFH concentration with the logarithm of chain length full^ s a linear-t^ ting relationship with a slope equaling −1. Furthermore, the variation of the average volume fraction of stickers at the micellar core (AVFSM) with polymer concentration and chain length is focused in the system at Tm. It is founded by calculations that the above behavior of AVFSM, is explained in terms of intrachain and interchain associations. Використовуючи ґраткову модель самоузгодженого поля, вивчається вплив концентрацiї полiмера i довжини ланцюга на агрегацiю в асоцiативних полiмерних розчинах. У системах з рiзною довжиною ланцюга спостерiгається тiльки двi неоднорiднi морфологiї, а саме мiкрофлуктуацiйна однорiдна (MFH) i мiцелярна морфологiї. Температури, при яких вище згаданi двi морфологiї виникають впер-ше i позначаються як TMFH i Tm, вiдповiдно, є незалежними вiд концентрацiї полiмера i довжини ланцюга. Змiна логарифма критичної концентрацiї MFH зi змiною логарифма довжини ланцюга задовiльняє спiввiдношенню лiнiйного допасування з нахилом рiвним −1. Крiм того, змiна середньої об’ємної фракцiї стiкерiв при мiцелярному корi (AVFSM) з концентрацiєю полiмера i довжиною ланцюга сфокусована в системi при Tm. Знайдено шляхом розрахункiв, що вище згадана поведiнка AVFSM пояснюється в термiнах iнтраланцюгових та iнтерланцюгових асоцiацiй.